Growth, yield and yield components of rice (Oryza sativa) as influenced by tillage methods and cultivars - SAINI, ANKIT; MANUJA, SANDEEP; SINGH, GURUDEV; UPADHYAY, R G; KUMAR, ANIL; SHARMA, R P (The Indian Journal of Agricultural Sciences, 2023)
Different tillage methods i.e. zero tillage, natural farming, reduced tillage and conventional tillage in combination with 3 rice varieties, viz. Sukara Dhan 1 (HPR 1156), Him Palam Dhan 1 (HPR 2656) and Him Palam Lal Dhan 1 (HPR 2795) were evaluated in terms of growth, yield attributes and yield of direct seeded rice at research farm of Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya, Palampur, Himachal Pradesh during rainy (kharif) season of 2020 and 2021. The experiment, was laid out in split plot design with tillage options in main plot and cultivars in subplot and replicated thrice. Findings exhibits that the, conventional tillage recorded significantly higher grain, straw and biological yield followed by reduced tillage and zero tillage while significantly lower values of all these traits were observed in natural farming during both the years of experimentation. Significantly greater and lower yields recorded in conventional tillage and natural farming treatments were due to the significantly higher and lower values of different yield attributes including number of panicles/m2, number of grains/panicle, grain weight/panicle and 1000-grain weight, observed in the respective treatments. From the present investigation it can be concluded that conventional tillage resulted in higher yield attributes and yield as compared to natural farming while lower values of yield attributes and yield were recorded under natural farming. Among different rice cultivars Him Palam Lal Dhan 1 was found superior than Sukara Dhan 1 and Him Palam Dhan 1.